Aquaporins can be involved in the swelling caused by shiga toxin type 2 on hgec and hk-2 cells - Gomez, Fernando Daniel (2021)
Hemolytic uremic syndrome related to Shiga toxin?producing Escherichiacoli (STEC-HUS) is the principal etiology of acute kidney injuryin children in Argentina.Previously, we demonstrated that Shiga toxin type 2 (Stx2) damageshuman glomerular endothelial cells (HGEC) and HK-2 human proximaltubular epithelial cell line by inducing swelling and detachment.In this work, we analyzed cell volume changes of HGEC and HK-2exposed or not to Stx2 or a hypoosmotic (HYPO) medium, in thepresence or not of aquaporins (AQPs) inhibitors (mercuric chloride:HgCl2 and tetraethylammonium: TEA), or an inhibitor of Stx2 receptor(Gb3) synthesis, Eliglustat (EG). For controls, an isosmotic (ISO)medium was used.Cells were grown on 12 well plates and pretreated for 30 minuteswith HgCl2 (10 μM) or TEA (100 μM) or pretreated during 24 h withEG (10 μM). Then, HGEC and HK-2 were incubated with Stx2 (50μM) for an additional 40 minutes. Cell volume was analyzed by lightmicroscopy and measuring cell area by using Image J software.After Stx2 and HYPO medium treatments, a significant increase inthe cell volume of HGEC (Stx2: 42%; HYPO: 36%, n= 3, p<0.05) andHK-2 (Stx2: 70%; HYPO: 55%, n= 3, p<0.05) was detected respectto ISO medium. However, when HGEC and HK-2 were pretreatedwith HgCl2 or TEA a significant swelling prevention was obtained forHGEC (Stx2+HgCl2:100%; Stx2+TEA:86%; HYPO+HgCl2: 42.5%;HYPO+TEA: 83%, n=3, p<0.05) and HK-2 (Stx2+HgCl2: 90%; Stx-2+TEA: 85%; HYPO+HgCl2: 55%; HYPO+TEA: 75%, n=3, p<0.05).In addition, EG also was able to prevent HK-2 swelling in 87 % (n=1)with respect to Stx2 treatment.Results show that AQPs may be involved in the water movement insideHGEC and HK-2 induced by Stx2, since HgCl2 and TEA avoidedthis effect. Furthermore, binding of Stx2 to Gb3 could be the initialstep for the development of cellular mechanisms that possibly triggerthe entry of solutes into the cells and the consequent osmoticgradient responsible for the hypotonic effect.